2002
DOI: 10.1111/j.1151-2916.2002.tb00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Phases in Ti3SiC2 Synthesis from Ti/SiC/C Mixtures Studied by Time‐Resolved Neutron Diffraction

Abstract: The reactive sintering of 3Ti/SiC/C to form the layered ternary carbide Ti3SiC2 was studied in situ by time‐resolved neutron powder diffraction. A number of intermediate processes occur during the synthesis beginning with the α‐β transition in Ti. Concurrent with the α‐β transition, two intermediate phases, TiCx and Ti5Si3Cx (x≤ 1), form. These phases account for almost the entire sample in the range 1500–1600°C beyond which they react with each other and a small amount of free C to form the product phase Ti3S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 15 publications
6
48
0
2
Order By: Relevance
“…It has a combination of a high melting point (2403 K), a low density (4.32 g/cm 3 ), high hardness (11.3 GPa), and a relatively high Young's modulus (225 GPa) [1]. More recently, Ti 5 Si 3 was identified as an intermediate phase in the synthesis of titanium silicon carbide (Ti 3 SiC 2 ) [3,4]. This lamellar carbide also exhibits many useful properties, most readily summarised as a unique combination of metallic and ceramic characteristics [5].…”
Section: Introductionmentioning
confidence: 98%
“…It has a combination of a high melting point (2403 K), a low density (4.32 g/cm 3 ), high hardness (11.3 GPa), and a relatively high Young's modulus (225 GPa) [1]. More recently, Ti 5 Si 3 was identified as an intermediate phase in the synthesis of titanium silicon carbide (Ti 3 SiC 2 ) [3,4]. This lamellar carbide also exhibits many useful properties, most readily summarised as a unique combination of metallic and ceramic characteristics [5].…”
Section: Introductionmentioning
confidence: 98%
“…a layered, ternary carbide (or nitride) of general chemical formula M n À 1 AX n where M is an early transition metal, A is an element from groups 12-16 in the periodic table of the elements, X is either carbon or nitrogen and n is an integer 1-3. There is consensus in the literature, with some minor variations, on the route of formation of Ti 3 SiC 2 from powder mixtures including Ti metal, such as Ti/SiC/C [7,8], Ti/C/SiC [6,9,10], Ti/Si/C [11,12], Ti/Si/C [13][14][15], Ti/Si/TiC [16,17] or Ti/Si/TiC [18][19][20]. This reaction pathway includes the formation of Ti 5 Si 3 C x as a necessary intermediate phase for the formation of Ti 3 SiC 2 [9,10]. In TiC/Si powders, however, Ti 5 Si 3 C x has not been observed.…”
Section: Introductionmentioning
confidence: 99%
“…The typical product obtained by Riley et al [25] contained Ti 3 SiC 2 about 78 wt.%. Based upon the investigation using in situ neutron diffraction for the 3Ti-SiC-C system, it was suggested that with no evidence of liquid phases, a solidstate reaction mechanism with two intermediate phases TiC x and Ti 5 Si 3 C x was proposed for the formation of Ti 3 SiC 2 [30,31].…”
Section: Introductionmentioning
confidence: 99%